2017
DOI: 10.3390/nu9080860
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Fat-Soluble Vitamins in the Belgian Population: Adequacy and Contribution of Foods, Fortified Foods and Supplements

Abstract: A key challenge of public health nutrition is to provide the majority of the population with a sufficient level of micronutrients while preventing high-consumers from exceeding the tolerable upper intake level. Data of the 2014 Belgian food consumption survey (n = 3200) were used to assess fat-soluble vitamin (vitamins A, D, E and K) intake from the consumption of foods, fortified foods and supplements. This study revealed inadequate intakes for vitamin A, from all sources, in the entire Belgian population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Although in the present study vitamin D concentrations were not associated with exacerbations, as assessed on the basis of hospitalizations, emergency room visits, and oral corticosteroid use, many studies have indicated such an association. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Although in the present study vitamin D concentrations were not associated with exacerbations, as assessed on the basis of hospitalizations, emergency room visits, and oral corticosteroid use, many studies have indicated such an association. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…The mean intakes ranged in children and adolescents (4–17 years) from 1.5 to 4.8 μg/day, and in adults from 0.8 to 6 μg/day [27]. The most recent data from a Spanish study (ANIBES) showed the total mean intake of vitamin D in the population was 4.4 ± 0.1 μg/day [28], and a similar Belgian study (VITADEK) showed the mean intake of vitamin D from natural and fortified foods (without supplements) was 3.37–4.41 μg/day in men aged 3–64 years and 3.18–3.48 μg/day in women aged 3–64 years [29]. …”
Section: Discussionmentioning
confidence: 99%
“…After an extensive literature review, dietary intake data on vitamins A, D, E, and K in Belgian infants, toddlers, pregnant women, and lactating women was found to be limited. Nevertheless, Belgian dietary studies in young children (2.5–6 years) and women of reproductive age revealed inadequate vitamin A and D intake [ 11 , 16 ]. Inadequate consumption was related to unbalanced food consumption and unsatisfactory supplement compliance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Belgian dietary studies in young children (2.5–6 years) and women of reproductive age revealed inadequate vitamin A and D intake [ 11 , 16 ]. Inadequate consumption was related to unbalanced food consumption and unsatisfactory supplement compliance [ 16 ]. Plasma 25-hydroxyvitamin D (S-25(OH)D) is a biomarker for vitamin D status and reflects the availability of vitamin D in the body from both dietary and endogenous sources [ 8 ].…”
Section: Introductionmentioning
confidence: 99%